Introduction to Crystal Reports 2008 - Miles, Timothy J.; Safari eBooks ([S.l.] : CompuWorks, 2012)
"This course teaches the beginning user how to create useful reports using Crystal Reports 2008. The primary focus is to give you a solid foundation on effectively using the Crystal Reports interface and its many features. When completed, the student will understand how reports are generated and how to customize the output for practical, impressive reports. You will learn how to create a simple report, use formulas in a report, use conditional formatting, add parameters to a report, distribute data, enhance a report and much more."--Resource description page.
Title from title screen.
Publication information from resource description page (viewed Apr. 9, 2013).
Presenter, Timothy Miles.
Keywords: Crystal reports (Electronic resource); Business report writing -- Computer programs; Electronic books